THE FORMATION OF ISLAMIC PARTIES IN POST-INDEPENDENCE INDONESIA - Fajar, Arif; Nabila, Nabila; Nasikhin, Nasikhin; Fihris, Fihris (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2023)
This study aims to explain the formation of Islamic parties that were formed after independence, and to look at the political reality of Islamic parties from the Old Order to the New Order. Islamic political position in that period was relatively weak. Islamic parties at that time it was a minority political group in state institutions. As a minority group, they only play a driving role in giving an Islamic style to political developments in Indonesia as a logical consequence that must be accepted in the reality of political history. Only adapting to the new political system and order under one command. By using the literature study method, this study shows that; (1) Islamic parties that were established after independence (2) Dynamics of post-independence socio-cultural conditions (3) Post-independence government systems (4) Da'wah strategies carried out by Islamic parties (5) Challenges faced by Islamic parties when post-independence (6) Figures and Ulama' who influenced the post-independence period. This study is important to add to sources of study of Islamic history in Indonesia, especially the scarcity of themes regarding the formation of post-independence Islamic parties